PENGARUH CITRA MEREK, HARGA DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN JASA PENGIRIMAN J&T EXPRESS - Hastuti, Anik Puji; Rahayu, Listyowati Puji; Suryana, Alean Kistiani Hegy; Purwanto, Hari; Safitri, Unna Ria (EKOBIS, 2024)
The purpose of this study was to determine the influence of brand image, price and service quality on the purchase decision of delivery services at the J&T Express branch in Boyolali. The study's population was service users at the J&T Express branch in Boyolali. Data collection technique through the distribution of questionnaires with a sample of 100 respondents using the Accidental Sampling method. Using quantitative methods and descriptive analysis of case studies. Testing of data instruments is carried out with validity tests and reliability tests, for data analysis, normality tests, multicholinearity tests, heteroskedasticity tests, autocorrelation tests are used. The t test and the f test and the determination test (R2) are used for hypothesis testing. Validity tests, reliability tests and classical assumption tests whose data have been met are then processed to produce regression equations: Y = 3,455 + 0.168 X1 + 0.186 X2 + 0.535 X3. Partially the brand image and price variables do not affect the purchase decision variable, while the service quality variable affects the purchase decision variable indicated by hypothesis testing, namely test t. The results of the f test are shown simultaneously the influence of the three free variables on the bound variable. It is stated that the results of the determination test (R2) that the value of R Square is 0.599, which means that the variable bound by the purchase decision with a value of 59% is able to explain the three free variables and the value of the remaining 41% is explained by variables outside the study such as location, facilities and so on. Keywords: Brand Image, Price, Service Quality and Purchase Decision